2009
DOI: 10.1007/s00360-009-0352-6
|View full text |Cite
|
Sign up to set email alerts
|

Body and brain temperature coupling: the critical role of cerebral blood flow

Abstract: Direct measurements of deep-brain and body-core temperature were performed on rats to determine the influence of cerebral blood flow (CBF) on brain temperature regulation under static and dynamic conditions. Static changes of CBF were achieved using different anesthetics (chloral hydrate, CH; α-chloralose, αCS; and isoflurane, IF) with αCS causing larger decreases in CBF than CH and IF; dynamic changes were achieved by inducing transient hypercapnia (5% CO2 in 40% O2 and 55% N2). Initial deep-brain/body-core t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 48 publications
8
68
0
Order By: Relevance
“…Mäkinen et al (2006) observed that decreased skin temperatures and thermal sensations of cold were associated with longer response times and a decreased efficiency in the simple reaction time task which measures simple visuomotor response times. Also, our data agree with a recent Brazaitis et al (2014) study, where decrements in the reaction time were observed during the choice reaction task after intermittent immersion in bath water (14 °C).A series of studies raise the possibility that brain temperatures are somewhat independent from both core and oesophageal temperatures (Harris et al, 2008;Zhu et al, 2009). However, it is unknown how actually temperatures may differ across the brain regions and whether that pattern helps to account for the differential impact of cold exposure on different cognitive abilities.…”
supporting
confidence: 93%
“…Mäkinen et al (2006) observed that decreased skin temperatures and thermal sensations of cold were associated with longer response times and a decreased efficiency in the simple reaction time task which measures simple visuomotor response times. Also, our data agree with a recent Brazaitis et al (2014) study, where decrements in the reaction time were observed during the choice reaction task after intermittent immersion in bath water (14 °C).A series of studies raise the possibility that brain temperatures are somewhat independent from both core and oesophageal temperatures (Harris et al, 2008;Zhu et al, 2009). However, it is unknown how actually temperatures may differ across the brain regions and whether that pattern helps to account for the differential impact of cold exposure on different cognitive abilities.…”
supporting
confidence: 93%
“…Briefly, after initial induction of anesthesia with a ketamine-xylazine mixture (a 60 mg/kg dose of ketamine plus a 10 mg/kg dose of xylazine, intraperitoneally) (24), the rat was shaved, transported to the surgery table in a dedicated surgery room, and fixed on the platform with a warm pad (model 69001; RWD Life Science) to maintain the body temperature throughout the procedure. The animal received an intraperitoneal injection of 10% chloral hydrate (350 mg/kg) (24). Focal brain ischemia was induced by the intraluminal suture technique.…”
Section: Induction Of Middle Cerebral Artery Occlusionmentioning
confidence: 99%
“…Intraoperative parameters may include heart rate, blood pressure, temperature, blood gas analysis, electrocardiogram, and electroencephalogram activity. Some recommend the measurement of both rectal and cranial temperatures (Busto et al, 1989), although there has been excellent correlation between the two with isofluorane anesthetic (R 2 = 0.9996) (Zhu et al, 2009), suggesting that invasive brain temperature monitoring is unnecessary. The measurement of CBF can be used to monitor cerebral ischemia, seizures, and the effect of drugs on CBF; although, as earlier described, true ischemia is not thought to occur in ICH unless the hematoma is of significant size .…”
Section: Minimizing Excess Inflammationmentioning
confidence: 99%